Strategic Human Resource Management: Enhancing Operational Effectiveness in Madrasah - Hadi, Samsul (At-Tarbiyat, 2025)
This research aims to explore and analyze the implementation and effectiveness of human resource management in the context of educational institutions in Madrasah. This research use a qualitative method with a descriptive approach. The data collection techniques used in this research were interviews and documentation. The validity of this research was also obtained through source triangulation techniques, namely comparing the information obtained by the author with the theory used. The informants in this research consisted of the head of the madrasah, head of administration, and teachers also. Data analysis was carried out through reduction data , presentation data , and drawing conclusions. The research result shows that the implementation of human resource management at MI Miftahul Huda Ngawi has gone well, with a focus on four aspects, namely recruitment, training, compensation and dismissal. The four main aspects studied by the author are in accordance with Schuler's theory and the opinion of the three informants studied. It hope that the results of this research can contribute to the development of human resource management theory and practice and provide useful guidance for educational institutions in improving the quality and effectiveness of human resource management.